1959
DOI: 10.1007/bf02505455
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung der Strömung als ökologischer Faktor

Abstract: Baetis scambus Etn. und Baetis vernus Curt. 2. Ecdyonurus venosus Fbr. 3. Ephemerella ignita Poda. . . . 4. Rithrogena cf. semicolorata Curt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
1
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 35 publications
(16 reference statements)
4
48
1
3
Order By: Relevance
“…Within the benthic macroinvertebrates, stoneflies are selected for evaluation of long-term changes [8]. Stoneflies are useful biological indicators of river quality, reflecting stream degradation, land use, and deforestation [9,10].Ambühl [11] and Egglishaw [12] relate the distribution of several macroinvertebrate species to current water velocity and substrata. Egglishaw [12] showed that, even in what was apparently a fairly uniform stretch of riffle, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the benthic macroinvertebrates, stoneflies are selected for evaluation of long-term changes [8]. Stoneflies are useful biological indicators of river quality, reflecting stream degradation, land use, and deforestation [9,10].Ambühl [11] and Egglishaw [12] relate the distribution of several macroinvertebrate species to current water velocity and substrata. Egglishaw [12] showed that, even in what was apparently a fairly uniform stretch of riffle, i.e.…”
mentioning
confidence: 99%
“…Ambühl [11] and Egglishaw [12] relate the distribution of several macroinvertebrate species to current water velocity and substrata. Egglishaw [12] showed that, even in what was apparently a fairly uniform stretch of riffle, i.e.…”
mentioning
confidence: 99%
“…The boundary layer at the liquid -solid interface is thought to be an important habitat for lotic microbial and invertebrate communities (Ambühl 1959, Schwoerbel 1994. Although the flow velocity decreases exponentially at the interface, the laminar flow at the surface can become turbulent due to surface roughness (Oertel et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the flow velocity decreases asymptotically from the surface towards the bottom. A few millimetres above the bottom, the flow velocity is very low (Ambühl 1959). This region is called the boundary layer and serves as a refuge for torrenticole macrofauna (Vogel 1981, Koehl 1984, Prandtl et al 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Although some information is available on the efffect of surface topography on hydrodynamics in the vicinity of macrofauna (e.g. Ambühl 1959, Statzner & Holm 1989, Hunt 2004, the 2 to 5 µm water layer in which nanoprotists live remains to be investigated. To ABSTRACT: Surfaces in running water are covered by a boundary layer.…”
Section: Introductionmentioning
confidence: 99%